Antifungal Mechanism and Efficacy of Kojic Acid for the Control of Sclerotinia sclerotiorum in Soybean - Zhu, Gui-Yang; Shi, Xin-Chi; Wang, Su-Yan; Wang, Bo; Laborda, Pedro (Frontiers in Plant Science, 2022)
Sclerotinia stem rot, which is caused by the fungal pathogen Sclerotinia sclerotiorum, is a soybean disease that results in enormous economic losses worldwide. The control of S. sclerotiorum is a difficult task due to the pathogen’s wide host range and its persistent structures, called sclerotia. In addition, there is lack of soybean cultivars with medium to high levels of resistance to S. sclerotiorum. In this work, kojic acid (KA), a natural bioactive compound commonly used in cosmetic industry, was evaluated for the management of Sclerotinia stem rot. Interestingly, KA showed strong antifungal activity against S. sclerotiorum by inhibiting chitin and melanin syntheses and, subsequently, sclerotia formation. The antifungal activity of KA was not obviously affected by pH, but was reduced in the presence of metal ions. Treatment with KA reduced the content of virulence factor oxalic acid in S. sclerotiorum secretions. Preventive applications of 50 mM KA (7.1 mg/mL) completely inhibited S. sclerotiorum symptoms in soybean; whereas, in curative applications, the combination of KA with prochloraz and carbendazim improved the efficacy of these commercial fungicides. Taken together, the antifungal activity of KA against S. sclerotiorum was studied for the first time, revealing new insights on the potential application of KA for the control of Sclerotinia stem rot in soybean.